2016
DOI: 10.1007/s10880-016-9457-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Web-Based Applications into Aged Care: Two Case Studies and Discussion

Abstract: In anticipation of the growing need for adequate mental health care for older adults in residential aged care facilities, psychologists are challenged to overcome several barriers that impede the uptake and delivery of their services in such settings. Information and communication technologies (ICT) have strong potential to overcome some of these barriers by supporting the delivery of evidence-based psychosocial treatments for common psychogeriatric issues. This paper presents two case studies that illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A case study by Rehm et al (2016) has identified that web-based applications would be feasible among PWD in residential aged care facilities. It has the potential to improve cognitive behavior and reduce depression and anxiety [ 23 ]. Our current study recognized that WBRT could potentially make a positive impact on improving mental health and positivity among PWD through the multi-sensory stimulation offered by reminiscence experiences in institutionalized healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…A case study by Rehm et al (2016) has identified that web-based applications would be feasible among PWD in residential aged care facilities. It has the potential to improve cognitive behavior and reduce depression and anxiety [ 23 ]. Our current study recognized that WBRT could potentially make a positive impact on improving mental health and positivity among PWD through the multi-sensory stimulation offered by reminiscence experiences in institutionalized healthcare settings.…”
Section: Discussionmentioning
confidence: 99%